Say cheese-- and die screaming! - Stine, R. L. (Stine, R. L. Goosebumps HorrorLand, 2009)
When Julie finds a strange camera, she discovers that the camera predicts bleak futures for anyone it takes pictures of. Later, Julie finds her way to HorrorLand and ends up falling into the Tunnel of Screams.